The goals and objectives of teaching English to law students - Akobirova, Sarvara (The Lingua Spectrum, 2024)
In this article, the main purpose of teaching foreign language (English) to non-philology students is to help them learn a foreign language for practical and communicative purposes, taking into account their professional needs, language as a tool for students and within their main specialties. Emphasis is placed on the development of applied functional skills. The goals and objectives of teaching English to legal students and the essence of professional terminology are discussed. The specific features of teaching a foreign language in the credit-module system for students studying law are determined. Several important stages of learning English for law students are analyzed. The article also emphasizes the importance of practical training and special classes for the development of reading and writing skills.